2021
DOI: 10.1016/j.jad.2021.07.072
|View full text |Cite|
|
Sign up to set email alerts
|

Network analysis of anxiety and depressive symptoms among nursing students during the COVID-19 pandemic

Abstract: Background: The 2019 coronavirus disease (COVID-19) pandemic has impacted the mental health and well-being of medical personnel, including nursing students. Network analysis provides a deeper characterization of symptom-symptom interactions in mental disorders. The aim of this study was to elucidate characteristics of anxiety and depressive symptom networks of Chinese nursing students during the COVID-19 pandemic. Method: A total of 932 nursing students were included. Anxiety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
70
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(88 citation statements)
references
References 68 publications
(91 reference statements)
15
70
1
2
Order By: Relevance
“…Liang et al (2020) also identified "tense" or "I found it difficult to relax" in a Chinese population, although they used DASS-21 to assess symptoms. Nevertheless, while symptoms like "sadness", "unstoppable worry", and "irritability" were identified in other studies (e.g., Bai et al, 2021;Kaiser et al, 2020;Ren et al, 2021), our study did not. Regarding bridge nodes that may play important roles in the development and maintenance of comorbidity, perhaps our biggest novel finding is anxiety symptom of "afraid" being the strongest bridge symptom.…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations
“…Liang et al (2020) also identified "tense" or "I found it difficult to relax" in a Chinese population, although they used DASS-21 to assess symptoms. Nevertheless, while symptoms like "sadness", "unstoppable worry", and "irritability" were identified in other studies (e.g., Bai et al, 2021;Kaiser et al, 2020;Ren et al, 2021), our study did not. Regarding bridge nodes that may play important roles in the development and maintenance of comorbidity, perhaps our biggest novel finding is anxiety symptom of "afraid" being the strongest bridge symptom.…”
Section: Discussioncontrasting
confidence: 88%
“…This finding generates the hypothesis that alleviating this symptom in students suffering from anxiety may reduce the likelihood of their developing comorbid depressive symptoms. A closer examination reveals that except for anxiety nodes, "afraid" is most strongly connected to depressive symptom of "worthlessness", which was the most strongly connected node to "suicide", a finding similar to Bai et al (2021). In other words, feeling afraid or fearful when anticipating the future is tied to worthlessness and suicidal ideation.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Such a correlation between these two mental health problem measures supports some empirical research exploring the comorbidity between anxiety and depression symptoms (measured by the GAD-7 and PHQ-9). For example, increasing studies found that the symptoms of anxiety (measured by the GAD-7) and depression (measured by the PHQ-9) are intercorrelated and directly interacted [ 42 , 43 , 44 ]. Moreover, researchers have found the GAD-7 performed well beyond measuring generalized anxiety disorder, but is also a useful measure in the mixed anxiety–depression sample [ 12 ].…”
Section: Discussionmentioning
confidence: 99%